Distributed Coordinated Dispatch Model for Multi-area Interconnected Integrated Energy Systems Based on Sequential Cone Programming - Yujie REN; Yuhan HUANG; Zhenbo WEI (工程科学与技术)
Multi-area energy exchange addresses the reverse distribution of energy resources and demand in various regions of China through resource and risk sharing. The complementarity and mutual support between different energy sources effectively alleviate the imbalance between the pace of wind power installation and its consumption level. Based on this, this study proposes a distributed coordinated dispatch model for multi-area integrated electricity and natural gas systems (IEGS) using sequential cone programming (SCP) within the context of integrated energy systems. Firstly, considering the economic benefits of day-ahead dispatch, an IEGS economic dispatch model is established, targeting the minimization of total energy consumption costs. Secondly, given the positive impact of the flexible power adjustment characteristics of DC tie-lines on renewable energy consumption, DC tie-lines and pipelines are utilized as carriers for energy flow transmission and resource sharing between regions and are subjected to modeling and analysis. In addition, a second-order cone relaxation method based on SCP is proposed to handle the gas network flow in the IEGS economic dispatch model, linearizing the flow constraints and reducing the relaxation gap caused by optimization processing. Finally, the analytical target cascading (ATC) method is utilized to demonstrate the autonomous capacity of different areas to solve the distributed dispatch model after decoupling shared variables between areas and establishing the distributed coordination dispatch. Under the circumstances of two-region and three-region interconnected IEGS, the impact of different interconnection methods and gas network flow processing methods on dispatch results is verified, and the difference between centralized and distributed algorithms in handling multi-area integrated problems is compared. The simulation results indicated that the second-order cone relaxation based on SCP significantly ameliorates the relaxation gap. The economic efficiency of power grid operation is improved, and the wind curtailment rate is decreased due to DC tie-lines and pipelines. The solution of the distributed algorithm based on ATC is close to the global optimal solution of the distributed algorithm. The distributed coordinated dispatch model proposed in this study is reasonably designed and provides a reference for establishing a coordinated dispatch model for integrated energy systems considering integrating new energy.